Will informing pregnant women about proper seat belt usage lead to fewer maternal and fetal injuries from motor vehicle accidents?. Issue 7 (July 2018) - Werth, Lynne; LaBounty, LaShell
Abstract : EVIDENCE‐BASED ANSWER : No trials have specifically investigated whether informing pregnant women about proper seat belt use leads to decreased maternal and fetal injuries. However, pregnant women receiving information about seat belt use are more likely to use and correctly place seat belts (SOR: B, prospective cohort study). Wearing seatbelts is associated with an 84% risk reduction in adverse fetal outcomes in motor vehicle accidents, whereas for women who were unrestrained drivers in a motor vehicle accident during pregnancy, stillbirth is nearly 3 times more common (SOR: B, 2 retrospective cohort studies).